Andante Spianato en Grande Polonaise opus 22; Polonaise d-mineur opus 71 nr. 1; Polonaise B Majeur opus posthuum; 2 Polonaises opus 26 - Chopin, Frédéric 1810-1849; Czerny-Stefańska, Halina 1922-2001; Rowicki, Witold; Warsaw National Philharmonic Orchestra (Poland) (Hamburg Telefunken)
Halina Czerny-Stefańska was a Polish pianist who studied with her father, Stanisław Szwarcenberg-Czerny, as well as with Alfred Cortot at the École Normale de Musique in Paris, and later with Józef Turczyński and Zbigniew Drzewiecki in Warsaw. She was a joint First Prize winner at the IV International Chopin Piano Competition in Warsaw in 1949, sharing this prize with Bella Davidovich. Her repertoire was restricted to few composers other than Frédéric Chopin and even her Chopin repertoire was not large.
Keywords: 19th Century (1801-1900); Polonaise; Andante; Keyboard music; Piano; Poland; Paris (France)